Digital maturity of construction companies: economic and managerial issues, analytical indicators, and adaptation scenarios - Fesun , Artem; Kucherenko , Oleksandr; Fedorov , Viacheslav; Krupnyk , Danylo; Kostenko , Denys (Ways to Improve Construction Efficiency, 2024)
The article examines digital modernization as a key vector for the transformation of operational systems in construction development enterprises under unstable business environments, global challenges, and post-crisis recovery. The relevance of the study is driven by the need to adapt the construction industry to modern operational conditions, particularly digitalization, innovative integration, and the shift in management paradigms in response to economic, technological, and social risks. The paper outlines the main problems accompanying digital transformation: fragmentation of internal processes, low level of digital competence among personnel, an underdeveloped regulatory framework, and lack of systematic state support. To address these challenges, a comprehensive approach to forming a digital ecosystem in construction development is proposed, based on the integration of digital technologies, management platforms, cross-sectoral interaction, and the application of ESG-oriented practices. The study presents a selection of formalized indicators for digital transformation of operational systems, which allow for an objective assessment of digital maturity, flexibility, adaptability, and the efficiency of business processes. Based on the analysis of scientific sources and practical trends, the paper substantiates the feasibility of using data analytics, digital twins, smart contracts, cloud-based solutions, and geo-analytical platforms to ensure continuous development and enhance the competitiveness of construction enterprises. It concludes that strategically oriented digital transformation of operational systems in the construction sector creates the foundation for building a flexible, resilient, and innovation-driven environment capable of responding effectively to current challenges and shaping new quality standards in development activities.